The New Terrain of International Law - Karen J. Alter (Princeton University Press, 2014)
This book is motivated by the changing world around us. The growing role of judges, both domestic and international, is self-evident. In the United States and Europe courts review most major policy initiatives, and judicial rulings are front-page news. In many other parts of the world judges are also becoming increasingly emboldened, willing to challenge powerful individuals and governments. International courts are part of this global trend and a powerful symbol that law and legalism have become part of foreign affairs and international politics. What draws the attention of international relations scholars is the fact that international courts increasingly speak to issues that used to fall exclusively within the national domain. There are literally thousands of international judicial rulings reviewing the human rights and economic practices of governments. International adjudication has even entered the might-equals- right world of security relations. These developments are further evidence of evolving norms of state sovereignty. Despite clear changes in the world around us, much of the academy remains trapped in old ways of thinking. The new international courts are quite different from the archetype in most scholarsâ€™ headsâ€”the International Court of Justiceâ€”and the substance of international law has also changed, becoming more detailed and far reaching in its scope. International relations and international law scholarship is yet to catch up. Most international relations scholars still assume that international courts exist primarily to resolve disputes between states, that the desires governments express unquestionably reflect â€œthe national interest,â€ and that the wishes of powerful governments invariably do or should prevail. Of course governments remain key actors in international politics. World leaders dominate the global bully pulpit, and usually governments are the only voting participants within international institutions. Moreover, it is increasingly clear that the only thing worse than a state with a predatory leader is the chaos of a country lacking a government. Governments are and will remain essential actors in domestic and international politics.